PENCEGAHAN PENYAKIT RABIES DI WILAYAH KERJA PUSKESMAS TOMONI TIMUR TAHUN 2020 - Armawati Abidin; Anas Budi (Nurse and Health: Jurnal Keperawatan, 2021)
Background: Rabies is a deadly disease that is transmitted from animals to humans and attacks the central nervous system (WHO, 2016). Data reported by the World Animal Health Organization (OIE) revealed that the global human death rate due to rabies is almost 70 thousand per year. In other words, every ten minutes one person in the world dies from the virus. Objectives: This study aimed to find out the knowledge and prevention of rabies carried out by the community around the East Tomoni Public Health Center. Methods: This study was conducted in the working area of East Tomoni Public Health Center by involving 390 participants in August 2020. Data was collected using simple random sampling. The instrument of this study is questionnaire. Statistical test method used to know independent variables are univariat analysis and bivariat analysis. Results: The majority of good knowledge as much as 351 (90%) respondents were less Knowledge while 39 (10%) respondents. Good attitude as many as 318 (81.5%) Respondents have a pretty good attitude as many as 72 (18.5%) Respondents. Good rabies prevention measures were 347 respondents (88.9%) while those who had less rabies prevention measures were 43 (11.02%) respondents. The results of the study using the Pearson Chi-Square test showed that the level of knowledge was p-value = 0.000 (α < 0.05) means there is a relationship between the level of knowledge and rabies prevention measures in the work area of ​​the Tomoni Timur Public Health Center, whereas, the attitude with the Pearson Chi-Square test shows that the attitude of p-value = 0.000 (α < 0.05) means that there is a relationship between attitude and rabies prevention measures in the working area of ​​the Tomoni Community Health Center. Conclusion: There is a relationship between knowledge and attitudes of the community and rabies prevention in the East Tomoni Community Health Center.